Letter to Dr. TS Osdene, Chairman of Center for Indoor Air Research from Richard Dempster, President of Environmental Air Control, Incorporated - DEMPSTER, RICHARD (Tufts Archival Research Center, 2007)
Marginalia; Letter from Richard Dempster, President of Environmental Air Control, Incorporated to the chairman of the Center for Indoor Air Research (CIAR) regarding CIAR’s interest in the Environmental Air Control, Incorporated testing and analysis of indoor air quality. Stresses the fact that there has been little research conducted on the impact of environmental tobacco smoke on the quality of indoor air and that tobacco smoke may be only a minor risk.